2018
DOI: 10.1016/j.worlddev.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Natural disasters, social protection, and risk perceptions

Abstract: Natural disasters give rise to loss and damage and may affect subjective expectations about the prevalence and severity of future disasters. These expectations might then in turn shape individuals’ investment behaviors, potentially affecting their incomes in subsequent years. As part of an emerging literature on endogenous preferences, economists have begun studying the consequences that exposure to natural disasters have on risk attitudes, perceptions, and behavior. We add to this field by studying the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(63 citation statements)
references
References 74 publications
(77 reference statements)
3
56
2
2
Order By: Relevance
“…Most of the risk-tolerant farmers (red points) are located to the right of the first dimension, exhibiting a higher perception of the weather patterns related to climate change, compared to the risk-averse farmers. This result is similar to the finding of Pomareda (2008) [71] and Brown et al (2017), who found that effect of natural shocks affects risk attitudes and perceptions [72]. Furthermore, risk-tolerant farmers (red points) are more concentrated in the upper part of the second dimension, showing that they perceive to a greater extent that climate change has a high impact on their production.…”
Section: Risk Heterogeneity Analysissupporting
confidence: 89%
“…Most of the risk-tolerant farmers (red points) are located to the right of the first dimension, exhibiting a higher perception of the weather patterns related to climate change, compared to the risk-averse farmers. This result is similar to the finding of Pomareda (2008) [71] and Brown et al (2017), who found that effect of natural shocks affects risk attitudes and perceptions [72]. Furthermore, risk-tolerant farmers (red points) are more concentrated in the upper part of the second dimension, showing that they perceive to a greater extent that climate change has a high impact on their production.…”
Section: Risk Heterogeneity Analysissupporting
confidence: 89%
“…According to Brown et al, respondent attitudes, perceptions, and behavior toward disasters can be affected by exposure to and experience with such events. However, this study did not measure respondents' experience and exposure [51]. This study only focused on a few geographical areas of Pakistan.…”
Section: Limitations and Strengths Of The Studymentioning
confidence: 99%
“…Academic institutions can contribute leadership and resources to societal disaster preparedness [53]. Several studies strongly recommended that continuous and consistent disaster knowledge, skills, and preparedness content be included in college curricula [50][51][52][53][54][55][56].…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
“…A number of studies have found that large unexpected negative shocks (e.g. natural disasters, stock market losses, experiences of violence) impact preferences, at least for some groups in the population (Eckel et al 2009;Malmendier and Nagel 2011;Callen et al 2014;Carvalho et al, 2016;Brown et al, 2016). These findings have led to development of theoretical models that incorporate history-dependence (Dillenberger and Rozen 2015).…”
Section: Introductionmentioning
confidence: 99%